PENGARUH DUKUNGAN ORGANISASI TERHADAP KOMITMEN ORGANISASIONAL DAN KINERJA PEGAWAI - Metria, Ketut; Riana, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.09.TAHUN 2018, 2018)
This study aims to analyze: (1) influence of organizational support to employee performance, (2) influence of organizational support to organizational commitment and (3) influence organizational commitment to employee performance. A total of 77 employees of the Department of Population and Civil Registration of Denpasar is used as a sample with sampling technique that is saturated sampling. The data obtained were analyzed by descriptive analysis and SEM-PLS. The result of this study found that organizational support had positive and significant effect on employee performance, with coefficient value was 0,389 and t statistics value was 4,086 (> t critical 1,96). The effect of organizational support on organizational commitment resulted in coefficient value of 0.634 and t statistics of 9.091 (> t critical 1.96) which means significant. Furthermore, organizational commitment also has a significant positive effect on employee performance, with coefficient value of 0.363 and t statistics value of 4.635 (> t critical 1.96). This study proves that employees who get support from the organization proved able to increase organizational commitment to work which implies to the better performance displayed by employees of the Department of Population and Civil Registration of Denpasar.